2020
DOI: 10.1097/md.0000000000018398
|View full text |Cite
|
Sign up to set email alerts
|

Association of 17q24 rs1859962 gene polymorphism with prostate cancer risk

Abstract: Background: Recently, several genome-wide association studies have demonstrated a cumulative association of 17q24 rs1859962 gene variants with prostate cancer (PCa) risk, but conflicting results on this issue have been reported. Hence, we performed a systematic literature review and meta-analysis to assess the association between 17q24 rs1859962 gene and PCa risk. Methods: Systematic literature searches were conducted with PubMed, EMBASE, Science Direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…PC susceptibility locus at 17q24 has also been pinpointed as another risk loci. In a recent meta-analysis of association of the variant rs1859962 with the risk of PC development, the authors found the rs1859962 [G] allele to be significantly associated with the risk of PC (77). The variant rs1859962 has been mapped to enhancer elements of these variants in a diverse racial and ethnic population by validation studies is much needed before risk loci can be utilized in PC risk modeling.…”
Section: Challenges and Future Perspectivementioning
confidence: 99%
“…PC susceptibility locus at 17q24 has also been pinpointed as another risk loci. In a recent meta-analysis of association of the variant rs1859962 with the risk of PC development, the authors found the rs1859962 [G] allele to be significantly associated with the risk of PC (77). The variant rs1859962 has been mapped to enhancer elements of these variants in a diverse racial and ethnic population by validation studies is much needed before risk loci can be utilized in PC risk modeling.…”
Section: Challenges and Future Perspectivementioning
confidence: 99%